Upaya Penguatan Toleransi Beragama Para Mahasantri Spiritualis Pondok Pesantren Jagad ‘Alimussirry (PPJA) Surabaya Indonesia - Putri, Meilinda; Hartono, Djoko (Kajian Moral dan Kewarganegaraan, 2025)
Islamic boarding schools are non-formal Islamic educational institutions, some still suspect that they teach and indoctrinate their students with intolerance. This study aims to determine the efforts to strengthen religious tolerance of spiritualist students of PPJA Surabaya Indonesia. The focus of the study is the efforts made to strengthen religious tolerance of spiritualist students and their categories. The type of research is mixed methods. The primary informants are 6 asatidz/murobbi/caretakers and the secondary informants are 57 students consisting of 37 non-formal S1 students and 20 non-formal S2 students. The researcher used systematic interviews as a method for obtaining data. After the data was obtained, the researcher analyzed it using qualitative descriptive methods using percentages, phenomenology, structural functionalism and critical analysis. The findings of this study are the forms of efforts to strengthen religious tolerance carried out by asatidz/murobbi/caretakers to spiritualist students of PPJA Surabaya Indonesia as follows. First, providing an understanding that Indonesia is not an Islamic country but is based on Pancasila. Second, providing an understanding that Indonesia has a variety of cultures, customs, beliefs and religions. Third, fostering an inclusive way of thinking. Fourth, instilling the values ​​of togetherness, mutual respect, and harmony between religious communities. Fifth, providing integral religious insight and understanding. Efforts to strengthen religious tolerance carried out by asatidz/murobbi/caretakers to non-formal S1 and S2 students at PPJA Surabaya Indonesia are in the frequent and very frequent categories.